#### Answer

0

#### Work Step by Step

We are given that $f(x)=x^{2}-9$, $g(x)=2x$, and $h(x)=x-3$.
We are asked to find the value of $(g-h)(-3)$. We know that $(g-h)(x)=g(x)-h(x)$.
Therefore, $(g-h)(-3)=(2(-3))-(-3-3)=(-6)-(-6)=-6+6=0$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.